Dynamics of Law Enforcement and Justice in the Era of Sustainable Development Goals (SDGs) 5.0 - Handiyani, Kris Novi (Semarang State University Undergraduate Law and Society Review, 2023)
The dynamics of law enforcement and justice in the context of Sustainable Development Goals (SDGs) 5.0 represent an evolving framework that emphasizes the integration of legal systems with global sustainability objectives. SDG 5, which focuses on achieving gender equality and empowering all women and girls, plays a central role in reshaping legal landscapes worldwide. As countries strive to align their legal practices with the SDGs, law enforcement agencies face new challenges and opportunities in addressing issues of gender-based violence, discrimination, and inequality. The era of SDGs 5.0 signifies a more comprehensive approach to justice, recognizing the intersectionality of legal rights, social justice, and environmental sustainability. The role of law enforcement agencies has expanded to encompass not only traditional criminal justice functions but also proactive engagement in social change. They are expected to enforce laws that promote gender equality, protect marginalized communities, and address emerging global issues such as climate justice and human rights. Furthermore, the evolving digital landscape and the increasing use of technology present both a challenge and an opportunity for law enforcement in ensuring justice and equity in a rapidly changing world. This paper examines the changing dynamics of law enforcement and justice in the era of SDGs 5.0, exploring how legal frameworks are adapting to meet the demands of sustainability, gender equality, and social justice. It highlights the need for an integrated approach that combines legal reform, capacity building, and community engagement to achieve the SDGs while ensuring justice for all.